2022
DOI: 10.18280/isi.270113
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency Identification Based Student Attendance System

Abstract: Attendance is a record tracking system used in organization. It is used in the educational sector to track students who attend classes as well as staffs attendance. This system is a form of inventory keeping system in school but instead of tracking goods, people are tracked. In Babcock the attendance system being used presently is conventional and very susceptible to attacks. Due to these, a system is created to curb these challenges. In this work an attendance system was created which receives data input from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Of course, making RFID devices fully compatible with the Microsoft Windows platform is a prerequisite for this. The solution of Izang et al [17] is to integrate all types of RFID devices (including current RFID devices, next-generation RFID devices, sensors, and EPC (Electronic Product Code) readers) by adding a software adaptation layer to the RFID device. Integration on the Microsoft Windows platform becomes a "plug-andplay" model.…”
Section: Related Workmentioning
confidence: 99%
“…Of course, making RFID devices fully compatible with the Microsoft Windows platform is a prerequisite for this. The solution of Izang et al [17] is to integrate all types of RFID devices (including current RFID devices, next-generation RFID devices, sensors, and EPC (Electronic Product Code) readers) by adding a software adaptation layer to the RFID device. Integration on the Microsoft Windows platform becomes a "plug-andplay" model.…”
Section: Related Workmentioning
confidence: 99%
“…It is feasible, however there is a threat that someone may utilize the MA's ID and passwords. There should be some sort of identification, such as a thumbprint, RFID, or face recognition like in [14,15]. It will be easier for teachers to believe and identify the MA.…”
Section: Finding 1: Flaws In Ssms App and Improvements For The New Fr...mentioning
confidence: 99%
“…The paper, presents the results of a pilot study conducted in a small organization, which showed that the system was effective in accurately tracking employee attendance and reducing the time and effort required for attendance tracking. There are several other studies which suggest the use of face recognition [10,11,13,14], RFID [12,15] and cloud computing [16] for monitoring system. Teachers' attendance is one of the components of the SSMS framework, but there are a number of problems with it as it is right now.…”
Section: Introductionmentioning
confidence: 99%
“…The above has paved the way for many companies to embrace new ideas in manufacturing wireless devices, particularly for consistent environmental conditions monitoring such as temperature and humidity. IoT devices built with wireless technologies like Bluetooth, wireless sensor networks (WSN), ZigBee, Wi-Fi, and Radio-frequency identification (RFID) [1][2][3][4] are widely employed to transmit sensor data from the end nodes to gateways and later sent to the application server for further use by authorized users. Several temperature and humidity monitoring systems have been developed using these wireless technologies and found applications in greenhouses [5], server rooms [6], data centers [7], and so on.…”
Section: Introductionmentioning
confidence: 99%